The Influence of User Generated Content (UGC), Product Quality, and Price on Purchase Interest of Ventela Shoes on TikTok Shop (Case Study on Digital Business Students of Stambuk 2021) - Tarigan, Sovia Loren Br; Prayogo, Rangga Restu (Lembaga Riset Mutiara Akbar (LARISMA), 2025)
This study aims to analyze the influence of User Generated Content (UGC), product quality, and price on purchase intention of Ventela shoes on the TikTok Shop platform, focusing on students of the Digital Business Study Program, class of 2021, at Universitas Negeri Medan. The background of the research is based on the growing phenomenon of TikTok Shop as a promotional and transactional e-commerce platform, and the rising popularity of Ventela as a local shoe brand among young consumers. This research uses a quantitative approach with data collected through questionnaires distributed to 109 students, with 86 respondents selected using purposive sampling. The data were analyzed using multiple linear regression to examine the influence of the independent variables (User Generated Content (UGC), product quality, and price) on the dependent variable (purchase intention). The results show that both partially and simultaneously, the three independent variables have a positive and significant influence on consumer purchase intention. These findings indicate that marketing strategies involving user-generated content, delivering quality products, and offering competitive pricing can effectively increase consumer interest in purchasing Ventela shoes via TikTok Shop.